EFEKTIVITAS CONTENT MARKETING, AFFILIATE MARKETING DAN LIVE STREAMING TIKTOK TERHADAP KEPUTUSAN PEMBELIAN BARENBLISS DI YOGYAKARTA - Nur Indah Widyawati; Asteria, Beta (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2024)
This research aims to determine the partial and simultaneous influence of content marketing, affiliate marketing and live streaming variables on Barenbliss purchasing decisions in Yogyakarta City. This study type is descriptive research with a quantitative approach. This research data is primary data taken through a questionnaire with 187 respondents using a technique of purposive sampling, which was then analyzed using the multiple linear regression method and hypothesis testing using SPSS 26 software. The research results obtained reveal that content marketing has a partial and significant impact on purchasing decisions, affiliate marketing has a partial and significant impact on purchasing decisions, and live streaming has a partial and significant impact on purchasing decisions.